Selection of Cuculidae to the Hosts Based on the External Characteristics of the Eggs - Wahyu Widodo; Priyantini Widiyaningrum (Biosaintifika: Journal of Biology & Biology Education, 2018)
Most of Cuculidae were known as parasitic birds, and they breed depend on their hosts. The obyective of the study was to know the external characteristics of the eggs of Cuculidae and their hosts which includes several components. e.i. shell color, shape, length, diameter and egg index. Those species of Cuculidae were Cacomantis merulinus lanceolatus, Cacomantis variolus sepulcralis, Surniculus lugubris lugubris and Eudynamys scolopaceus malayanus. There were 117 item of the bird egg reference’s collections in the Ornithology Laboratory, Zoology Division, Research Center for Biology, LIPI, in Cibinong, used as a research materials. Color and form the egg from every sample noted by pursuant to direct eyesight with the eye if possible and assisted with the magnifier, especially at flimsy spots egg’s color. The results shown that egg size of Cuculidae groups are bigger than their host eggs. Generally, the color variation of eggs of Cuculidae and their hosts are white or bluish white and their combination like as brown and greenish. The eggs shape of Cuculidae and host are similar, namely oval with IFO value about 73 - 75%.  The Cuculidae family pays attention to the color, spot pattern and shape of the host’s eggs in choosing the host for their own eggs. Though, there was also a tendency not to recognize the characteristic of the host’s egg. The studies represent an early stage in an attempt to strive the conservation of Cuculidae the bird hosts.